2022
DOI: 10.3389/fonc.2022.802009
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 and ω-6 Polyunsaturated Fatty Acids Regulate the Proliferation, Invasion and Angiogenesis of Gastric Cancer Through COX/PGE Signaling Pathway

Abstract: BackgroundThis study aims to investigate the effects of ω-3, ω-6 polyunsaturated fatty acids (PUFAs), and their middle metabolites prostaglandin (PGE)2 and PGE3 on proliferation, invasion, and angiogenesis formation of gastric cancer cells and to explore associated mechanism.MethodsRT-PCR and ELISA were used to detect the expression of cyclooxygenase (COX)-1 and COX-2 in gastric cancer cell lines. The effect of ω-3, ω-6, PGE2, and PGE3 on the proliferation, invasion, and angiogenesis of gastric cancer cells we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is not easy to perform studies regarding the effects of dietary components on human health; therefore researchers have conducted a large number of in vitro and animal-based studies. In one in vitro study, omega-3 and omega-6 PUFAs were found to increase or inhibit the metastatic potential of gastric cancer via COX-1/PGE3 and COX-2/PGE2, respectively ( 31 ). In an animal study, it was shown that the activation of TLR4 in rats is inhibited by a high dietary omega-6/omega-3 PUFA ratio, which in turn reduces their circulating lipid concentrations, improves their glucose tolerance, and ameliorates their insulin resistance ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is not easy to perform studies regarding the effects of dietary components on human health; therefore researchers have conducted a large number of in vitro and animal-based studies. In one in vitro study, omega-3 and omega-6 PUFAs were found to increase or inhibit the metastatic potential of gastric cancer via COX-1/PGE3 and COX-2/PGE2, respectively ( 31 ). In an animal study, it was shown that the activation of TLR4 in rats is inhibited by a high dietary omega-6/omega-3 PUFA ratio, which in turn reduces their circulating lipid concentrations, improves their glucose tolerance, and ameliorates their insulin resistance ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the intake of long-chain omega-3 fatty acids and MUFAs was negatively associated with liver cancer [ 64 ]. ω-6 PUFAs could enhance the metastatic ability of gastric cancer cells through the COX-2/PGE2 signaling pathway, whereas ω-3 PUFAs serve to inhibit that ability through the COX-1/PGE3 signaling axis [ 65 ]. In breast cancer cells, ω-3 PUFAs induced the downregulation of EZH2, thus exerting anticancer effects [ 66 ].…”
Section: Fatty Acids In the Diet And Their Relationship To Cancermentioning
confidence: 99%
“…Tumor cells can acquire migratory capacity, which promotes metastatic colonization ( 50 ). Notably, ω-6 polyunsaturated fatty acids (PUFAs) were found to enhance the metastatic potential of gastric cancer cells via COX-2/PGE2 ( 51 , 52 ). Thus, PGE2 has been shown to be a conventional target with pleiotropic effects in cancer onset and progression and can be used to develop novel potential treatments with clinical implications.…”
Section: The Role Played By Cyclooxygenase-2 In Different Diseasesmentioning
confidence: 99%